Cluster of three cases of invasive meningococcal disease in a preschool facility in West Bohemia, the Czech Republic - Pazdiora, P; Morávková, I; Bergerová, T; Struncová, V; Křížová, P; Musílek, M; Beneš, C (Folia microbiologica, 2013)
From 1993 to 2009, there was only one cluster of invasive meningococcal disease (IMD) reported in a community of children in the Czech Republic. This exceptional cluster that occurred in a preschool facility is the focus of this report. In response to the announcement of the disease, anti-epidemic precautions were put in place. Neisseria meningitidis isolates were delivered from local laboratories to the National Reference Laboratory for Meningococcal Infections in Prague. Phenotyping was performed there along with multilocus sequence typing. Related factors and microbiological results were analyzed retrospectively. In October 2009, three girls contracted IMD within a period of 1 week in a 42-member group in a preschool facility attached to the elementary school in Starý Plzenec-Sedlec. In relation to three cases of the disease, another 66 people were registered of which 58 underwent a microbiological examination. N. meningitidis was detected in a total of five (8.6 %) people. The National Reference Laboratory for Meningococcal Infections defined the type of the strain to be C: P1.18-1,34-2,38: F1-7: ST-467 (cc269) and penA27. Tests showed the precise identity of all strains obtained from the three sick children and of two strains contracted through contact with the preschool facility. Despite the complete recovery of all patients with no permanent damage, the need for rapid cooperation between clinical sites, diagnostic laboratories, and epidemiologists was confirmed.
Keywords: dospělí; meningitida bakteriální; Meningitis, Bacterial; dítě; předškolní dítě; Adult; mladý dospělý; zařízení denní péče pro děti; Adolescent; sepse; meningokokové infekce; Sepsis; shluková analýza; lidé; Meningococcal Infections; multilokusová sekvenční typizace; Child Day Care Centers; Czech Republic; Neisseria meningitidis; Child, Preschool; Young Adult; Česká republika; Multilocus Sequence Typing; lidé středního věku; Child; Cluster Analysis; Middle Aged; mladiství; Humans